Fermentation Experiment of Arabica Coffee (Coffea arabica L.) from Dolok Sanggul with Variation of Gas Condition at Isothermal Temperature - Rabiah Afifah Daulay; Moondra Zubir; Ani Sutiani; Jenny Lasria Florita Br.Tampubolon; Winda Silalahi; Amelia Rahmadhani; Muhammad Ali Athiya Zahran; Lisna Sevta Siburian (Indonesian Journal of Chemical Science and Technology (IJCST), 2025)
Indonesia is one of the largest coffee producing and exporting countries in the world. One of the types of coffee that is famous in Indonesia is arabica coffee. This study examines the impact of different gas environments (open, semi-closed, and closed) on the fermentation process of Arabica coffee beans (Coffea arabica L.) at various temperatures (40°C, 60°C, and 80°C). The key factors analyzed were the moisture content and pH levels of the beans after fermentation and roasting. The findings revealed that both gas environment and temperature had a significant effect on the moisture content and pH of the beans, with higher temperatures (80°C) leading to a faster reduction in moisture. Additionally, the pH level was higher under open gas conditions. This research offers valuable information on how fermentation conditions influence the chemical properties and qualities of Arabica coffee beans.